2018
DOI: 10.3126/hijost.v2i0.25837
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Overweight and Obesity among Women of Reproductive Age Residing in Dharan Sub-Metropolitan City, Nepal

Abstract: Overweight and obesity is an emerging public health issue in developed world and is also rapidly increasing in developing world. This study was carried out to determine the prevalence and associated risk factors of overweight and obesity among women of child bearing age. A cross sectional study was conducted among 206 women residing in Dharan Sub-Metropolitan city of eastern Nepal. BMI, waist circumference and waist to hip ratio were used as indicators for overweight and obesity based on WHO classification and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Age was found significantly associated with overweight, including obesity from studies in Nepal 22,18 and other different parts of the world. 23 The results of this study were also consistent with studies in India and Ghana, where in India women age 40-49 years were 12.35 times and age 30-39 years were 8.48 times more likely to be obese 21 and in Ghana women within the age 35-44 years had the highest odds (3.55, p=0.000) of being overweight or obese.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Age was found significantly associated with overweight, including obesity from studies in Nepal 22,18 and other different parts of the world. 23 The results of this study were also consistent with studies in India and Ghana, where in India women age 40-49 years were 12.35 times and age 30-39 years were 8.48 times more likely to be obese 21 and in Ghana women within the age 35-44 years had the highest odds (3.55, p=0.000) of being overweight or obese.…”
Section: Discussionmentioning
confidence: 93%
“…This study reported the prevalence of overweight/obesity to be 49. 17,18 Likewise, study among adults from India uttarakhand 19 and another study of Delhi reported 55.5% and 50.1% to be overweight including obesity respectively. 20 In contrast, this study reported higher prevalence of overweight and obesity among 15-49 years than the prevalence from the national level surveys NDHS 2016 and NNMSS 2016, which reported 22% of overweight/obese respectively among 15-49 non pregnant women.…”
Section: Discussionmentioning
confidence: 98%